Extremely Rare Intraoral Presentation of Localized Amyloidosis - Luka Morelato; Igor Smojver; Sven Seiwerth; Dragana Gabrić (Hindawi Limited, 2021)
Purpose. To present an extremely rare case of localized amyloidosis of the mucosa of the maxillary alveolar ridge. Case Report. A 71-year-old man was referred to the Department of Oral Surgery, School of Dental Medicine, University of Zagreb, for a persistent nodular formation in the edentulous ridge of the anterior maxillary region. The nodular formation had a reddish color, solid consistency, and an approximate size of 40×15 mm. Orthopantomographic imaging excluded bone resorption and defects. Histopathological assessments of the biopsy specimen showed that the stroma was occupied by a multiplied, partially hyalinized connective tissue. The samples were subsequently stained with Congo red, and collagen accumulation under polarized light showed an apple-green birefringence indicating amyloid. Subsequently, the nodular formation was completely excised and a maxillary total denture was made. The patient showed normal tissue healing with no sign of recurrence at a follow-up assessment 1.5 years after the procedure. Conclusion. This is only the third reported case of localized amyloidosis of the alveolar ridge mucosa. Histopathological analysis is the first step for diagnosis, but systemic tests, blood counts, urinalysis, bone marrow biopsy, electrocardiography, and digestive endoscopy are recommended to rule out a systemic disease.